Neutrophil-Lymphocyte Ratio as a Prognostic Marker for Inflammatory Status Among Patients with Diabetes Mellitus: Neutrophil-Lymphocyte Ratio as a Prognostic Marker for Inflammatory Status - Naz, Shereen; Ujjan, Ikram Din; Kadir, Sidra; Majeed, Sadia; Shaikh, Ifrah; Rajput, Asma (Pakistan Journal of Health Sciences, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder associated with systemic inflammation and multiple vascular complications. Identifying accessible and cost-effective biomarkers for inflammation can improve the management and prognosis of diabetic patients. Objectives: To evaluate the neutrophil to lymphocyte ratio (NLR) as a prognostic marker for inflammatory status in patients with diabetes mellitus. Methods: This cross-sectional analytical study included 212 diabetic patients recruited from Liaquat University Hospital, Hyderabad. Data were collected on demographics, clinical history, complications, and comorbidities. Blood samples were analyzed for complete blood count and C-reactive protein (CRP) to calculate NLR. Patients were categorized based on normal (≤3) or raised (>3) NLR. Statistical analysis was performed using SPSS version 21.0, with p<0.05 considered significant. Results: Of the 212 participants, 52.8% were female and 81.1% had Type 2 diabetes. Raised NLR was observed in 24.1% and elevated CRP in 40.1%. Neuropathy (34.4%) and nephropathy (24.5%) were the most frequent complications. Raised NLR was significantly associated with elevated CRP (p=0.012), diabetic nephropathy (p=0.03), and diabetic retinopathy (p=0.04), while no significant association was observed with gender, duration of diabetes, or hypertension. Conclusions: NLR is a cost-effective, readily available marker significantly associated with systemic inflammation and microvascular complications in diabetes. It holds promise for routine inflammatory screening in clinical settings.